Cross‐species chemogenomic profiling reveals evolutionarily conserved drug mode of action - Laura Kapitzky; Pedro Beltrao; Theresa J Berens; Nadine Gassner; Chunshui Zhou; Arthur Wüster; Julie Wu; M Madan Babu; Stephen J Elledge; David Toczyski; R Scott Lokey; Nevan J Krogan (Molecular Systems Biology)
Abstract We present a cross‐species chemogenomic screening platform using libraries of haploid deletion mutants from two yeast species, Saccharomyces cerevisiae and Schizosaccharomyces pombe. We screened a set of compounds of known and unknown mode of action (MoA) and derived quantitative drug scores (or D‐scores), identifying mutants that are either sensitive or resistant to particular compounds. We found that compound–functional module relationships are more conserved than individual compound–gene interactions between these two species. Furthermore, we observed that combining data from both species allows for more accurate prediction of MoA. Finally, using this platform, we identified a novel small molecule that acts as a DNA damaging agent and demonstrate that its MoA is conserved in human cells.